Comparison Between Ai Chi and Stroke Mass Exercise for Dynamic Balance Improvement in Stroke Patient - Junita Siusanti; I Made Widagda; Dodik Pramono (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives : To observe improvement of dynamic balance in stroke patients who get Ai chi exercise compare to stroke exercise in stroke patients with onset more than six months.Methods : 30 subjects who met the inclution criterias were divided into two groups, Ai chi and stroke mass exercise group. Each group got exercise three times a week for four weeks.A dynamic balance testwith the four square steps test was conducted before exercise program and at the end of the exercise.Results : FSST Ai Chi start 20.48 ± 10.86, FSST end 17.55± 12.24,( p.005), stroke gymnastic start 23.98±9.41, stroke gymnastic end 18.24 ± 8.45 (p.002). In the initial test for all subjects FSST results obtained mean 28.72± 37.25 seconds and the final test of 24.02 ± 35.16 seconds FFT 29 (.443),FTT end 29(.957)Conclusions : Ai chi and stroke exercise training improved dynamic balance of stroke patients with onset more than six months, and statistically there is no different balance dynamic improvement for bothexercise.Keywords : Stroke, Dynamic balance, The four square steps test, Stroke exercise (senam stroke), Ai chi.